Taqiyya in Islam and its Evidence in the Holy Qur'an and Sunnah (Journal of Misan Researches, 2025)
This research aims to provide a comprehensive study introducing the concept of taqiya, particularly from the perspective of the Shia Imami school, with the goal of clarifying its true meaning and dispelling any confusion surrounding it. The study also seeks to address the attempts to exploit this concept in a way that undermines the unity of Muslims. Additionally, it highlights that the intellectual discourse has gone through multiple stages of development, during which politics and political conflict, along with misunderstandings, have influenced the manipulation of religious concepts to serve the ruling power at the expense of the opposition, regardless of scientific or jurisprudential standards. Among these concepts that have been distorted due to political expediency is the principle of taqiya.This research emphasizes the importance of understanding taqiya as a fundamental means of protecting individuals from risks or threats to their life or honor, permissible only in cases of necessity and under the condition that its use does not lead to the corruption of religion or harm to society. Taqiya is not merely a temporary legislation but a core Islamic principle that emerged during the period of Islamic propagation, with its roots in the Quran and Hadith. The human need for it has been evident throughout history, and the Imams of the Ahl al-Bayt (peace be upon them) adopted this principle in response to unjust policies and deviations from the Quranic method and its values. Taqiya is not a Shiite innovation, as some may assume, but an integral part of the Islamic heritage. The practice of taqiya serves multiple objectives: it protects the soul from destruction, provides steadfastness in the face of falsehood, embodies courage and wisdom, offers a sense of security, and preserves Muslim unity. Furthermore, its proper application is considered an act of obedience to Allah, the Almighty